2019
DOI: 10.1002/srin.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Boron in Heat‐Treatable Steels: A Review

Abstract: The science and technology of boron addition to heat‐treatable steels are explained. The aim is to address the following: How to add boron to steel (i.e., the manufacturing aspects of boron addition to steel)? What precautions are necessary when alloying boron to steel, in terms of composition (mainly nitrogen, aluminum, and titanium contents), processing and heat treatment (i.e., material and process robustness and reproducibility for a consistent steel quality)? Where does boron go in steel (i.e., the state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 154 publications
0
21
1
Order By: Relevance
“…In contrast, alloy L4 is hyperstochiometrically alloyed with aluminum to completely ensure that boron nitride formation is not possible. In addition, investigations reported in the literature have shown that around 0.0030 wt% boron gives a saturation level of grain boundary strengthening, [29] although this cannot be rebutted or confirmed by this study. Nevertheless, boron effectively strengthens the grain boundaries and increases the impact energy.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast, alloy L4 is hyperstochiometrically alloyed with aluminum to completely ensure that boron nitride formation is not possible. In addition, investigations reported in the literature have shown that around 0.0030 wt% boron gives a saturation level of grain boundary strengthening, [29] although this cannot be rebutted or confirmed by this study. Nevertheless, boron effectively strengthens the grain boundaries and increases the impact energy.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, nitride-forming elements, such as titanium and aluminum, are alloyed, consuming the nitrogen and forming nitrides to keep the boron free. [29][30][31] Figure 8. Monotonic yield strengths from initial loading curve and cyclic yield strengths R* p0.2 from IST of the QþT steel 42CrMo4, [16] the LHD steel LHD-11, [19] and the alloys L1-L5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, combined alloying of Nb and B as well as Mo and B has been described in the literature as enhancing boron's hardenability effect [2][3][4][5][6]. Both elements prevent boron from forming boron carbides (Fe 23 (C,B) 6 ) in the austenite grain boundaries that would reduce solute boron's effect of obstructing ferrite nucleation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of boride is improved by modification of the alloy molten with V, Ti, and RE-Mg [ 17 ], which improves the toughness of a high boron iron-based alloy. Moreover, the addition of a small amount of Nb or Mo can help to enhance boron’s hardenability in the steel, and prevent boron from forming boron carbides in the grain boundary [ 18 , 19 , 20 , 21 ], thereby reducing the obstructing effect of solute boron on ferrite nucleation [ 22 ]. Except for these, the net-like Fe 2 B can be disconnected by high temperature austenization [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%